Sensitivity analysis of rectangular atomic force microscope cantilevers immersed in liquids based on the modified couple stress theory. (January 2016) - Lee, Haw-Long; Chang, Win-Jin
Highlights: This article is to study the sensitivity of an AFM cantilevers in liquids. The modified couple stress theory is adopted to study the sensitivity. This theory is more suitable for micro-structures than classical continuum theory. The theory contains a material length scale parameter. The parameter is difficult to obtain by experimental measurements. The optimal method is used to estimate the material length scale parameter. Abstract: The modified couple stress theory is adopted to study the sensitivity of a rectangular atomic force microscope (AFM) cantilever immersed in acetone, water, carbon tetrachloride ( C C l 4 ), and 1-butanol. The theory contains a material length scale parameter and considers the size effect in the analysis. However, this parameter is difficult to obtain via experimental measurements. In this study, a conjugate gradient method for the parameter estimation of the frequency equation is presented. The optimal method provides a quantitative approach for estimating the material length scale parameter based on the modified couple stress theory. The results show that the material length scale parameter of the AFM cantilever immersed in acetone, C C l 4, water, and 1-butanol is 0, 25, 116.3, and 471 nm, respectively. In addition, the vibration sensitivities of the AFM cantilever immersed in these liquids are investigated. The results are useful for the design of AFM cantilevers immersed in liquids.